FoCo: A Shiny App for Formative Assessment using Cognitive Diagnosis Modeling - Sanz, Susana; Kreitchmann, Rodrigo; Nájera, Pablo; Moreno, José David; Martínez Huertas, José Ángel; Sorrel, Miguel (Colegio Oficial de la Psicologia de Madrid, 2023)
Combining formative and summative evaluations could improve assessment. Cognitive diagnosis modeling (CDM) has been proposed as a tool for diagnosing students’ strengths and weaknesses in formative assessment. However,there is no user-friendly software to implement it. For this reason,a Shiny app,FoCo,has been developed (https://foco.shinyapps.io/FoCo/),to conduct CDM and classical test theory analyses. The responses from 86 undergraduate students to a research methods course examination were analyzed. Students’ strengths and needs were diagnosed concerning their dominance of the syllabus contents and the first three competencies in Bloom’s taxonomy. The validity of the results was analyzed. The exam showed acceptable about evaluating students’ knowledge,as students with similar scores showed different strengths and weaknesses. Additionally,these attributes were found to predict different relevant criteria. It is expected that FoCo’s easiness to use promotes the employment of CDM in real educational settings. © 2023 Colegio Oficial de la Psicología de Madrid.
[FoCo: una aplicación Shiny para la evaluación formativa usando modelos de diagnóstico cognitivo]
Keywords: Cognitive diagnosis modeling; Computer application; Formative assessment; Multiple-choice items; 58 Pedagogía; ODS 4 - Educación de calidad